How to design and evaluate research in education - Fraenkel, Jack R.; Wallen, Norman E; Hyun, Helen H (McGraw Hill LLC, 2023)
How to Design and Evaluate Research in Education covers each step of the research process and discusses the most widely used research methodologies. It provides a comprehensive introduction to education research. End-of-chapter worksheets, comprehensive coverage of data analysis, and research tips make the text appropriate for courses that focus on doing research and for those that stress how to understand research.